Assessment Tool of Portfolios: Enhancing Primary School Students’ English Reading Proficiency - Dewi, Ni Putu Artila; Suryantini, Ni Made Detri; Sintadewi, Ni Made Dita (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This study aims to explore the use of portfolios as an assessment tool to enhance primary school students’ English reading proficiency. Portfolio assessment offers a more comprehensive and continuous approach compared to traditional assessment methods, which tend to measure students’ abilities at a single point in time. By using portfolios, teachers can collect various types of student work that demonstrate their progress and understanding in reading, such as book summaries, text analyses, and personal reflections. This research employs a qualitative method. Data is collected through classroom observations, interviews with teachers, and analysis of students’ portfolio documents. The findings indicate that using portfolios as an assessment tool provides several significant benefits. First, portfolios allow for a more holistic evaluation of students’ reading abilities, encompassing various aspects such as text comprehension, critical analysis, and reflective skills. Second, portfolios offer students the opportunity to see and recognize their own progress, which can boost their motivation and confidence in learning. Overall, this study concludes that portfolios are an effective assessment tool for enhancing primary school students’ reading proficiency in English. The use of portfolios not only aids in more comprehensive assessment but also supports deeper and more sustained development of reading skills. Therefore, it is recommended that schools and educators consider integrating portfolios into their English teaching curriculum.